My Ramadan diary - Android based Islamic planner mobile application / Nur Syahmina Anuar - Anuar, Nur Syahmina (2021)
Ramadan is a major event for Muslims all over the world and just like any other event, it is best to prepare for it in advance with a daily action plan. The planning requires goals of education and thoughtful spiritual experience. To avoid disappointment and frustration at the end of the month, a daily action plan shall be devised to get the best out of Ramadan. However, there is problem arise when using paper planner for example it is not portable compare to digital planner where it can be access anyway by using mobile phone and computer. Other than that, paper based planner tend to get messy with frequent updates and it also does not have notification and reminder features to remind user for their appointments. Thus, this project aim is to develop a mobile application that allow user to plan, log their spiritual journey such as days fasted, prayers, taraweeh and other daily deeds besides achieving their daily goals during month of Ramadan. Target user for this project are Muslim individual in Malaysia. Platform that will be used for this project development is android mobile application. This project adopts the Mobile Application Development Life Cycle (MADLC) which comprises of seven stages. This project will be developed until testing phase only. In conclusion, this project can help Muslim individual to increase their productivity during Ramadan.